EFEKTIVITAS TEKNIK BERMAIN PERAN TERHADAP KEMAMPUAN BERBICARA SISWA KELAS XI SMA PGRI 2 PADANG - Nirmasari, Wulan; Asri, Yasnur; Adrias, Adrias (Pendidikan Bahasa Indonesia, 2013)
The back ground of this observe are. First a students are seace to get a bad response pens are not afraid to get a good response from their friends in the classroom. It is a major factor in students not confident expressing their ideas orally results through speaking activities. Second, lack of interest and attention of students in learning to talk like drama and role play. Third, the use of techniques that are less interesting and too monotonous to wear a long lesson. This research is quantitative research design types exsperimen. The population in this study were students of class XI SMA PGRI 2 Padang registered in 2011/2012. Number of students is 111 students spread into 3 classes. Sampling was done by purposive random sampling technique. Researchers determined that XI1 class is 31 people as the control class and the class that numbered 30 XI2 IPS as a second grade class experiment, the writers choose as a class sample.The results showed as follows. First, the results of speaking skills is known that the average ability of students to speak without using the technique of playing the role of class XI IPS1 with an average value of 62.90 which is in the range 56-65% which kualisifikasinya "enough". Second, the results in this study students speaking ability by using role-playing techniques class XI IPS 2 with an average value of 74.80 which is in the range 66-75% which kualisifikasinya "more than enough". Based on the classification results using the talk test konfersi 10 scale. Third, there are differences in student learning outcomes without the use of role playing techniques and by using the technique of playing a role in learning speaking class XI SMA PGRI 2 Padang significantly from the use of techniques of playing the role of t-test results on the level of 95% (Î± = 0, 05) t = 3.73 t table = 1.645 thus HI accepted.